Galanin Receptor 2 Is Involved in Galanin-Induced Analgesic Effect by Activating PKC and CaMKII in the Nucleus Accumbens of Inflammatory Pain Rats - Li, Mengnan; Zhang, Xiaomin; Li, Chongyang; Liu, Yanan; Yang, Shuang; Xu, Shilian (Frontiers in Neuroscience, 2021)
It has been reported that galanin has an analgesic effect via activating galanin receptors (GALRs). This study focused on the involvement of GALR2 in the galanin-induced analgesic effect and its signalling mechanism in the nucleus accumbens (NAc) of inflammatory rats. Animal models were established through injecting carrageenan into the left plantar hind paw of rats. The results showed that GALR2 antagonist M871 weakened partially the galanin-caused increases in hind paw withdrawal latencies (HWLs) to both mechanical and thermal stimulation. Moreover, the GALR2 agonist M1145 prolonged the HWLs, while M871 blocked the M1145-induced increases in HWLs of inflammatory rats. Western blotting showed that the phosphorylation of calcium/calmodulin-dependent protein kinase II (p-CaMKII) and protein kinase C (p-PKC) in the NAc were upregulated after carrageenan injection, while p-PKC and p-CaMKII were downregulated after intra-NAc administration of M871. Furthermore, the CaMKII inhibitor KN93 and the PKC inhibitor GO6983 attenuated the M1145-caused analgesic effect in the NAc of rats with inflammation. These results prove that GALR2 is involved in the galanin-caused analgesic effect by activating CaMKII and PKC in the NAc of inflammatory pain rats, implying that GALR agonists probably are potent therapeutic options for inflammatory pain.